ANALISIS KESULITAN SISWA DALAM MENYELESAIKAN LUAS PERMUKAAN DAN VOLUME PRISMA - Fadilah, Julva Rizky; Muhtadi, Dedi; Sukirwan (Program Studi Tadris Matematika dan Tadris Ilmu Pengetahuan Alam, Fakultas Tarbiyah dan Ilmu Keguruan (FTIK), Universitas Islam Negeri (UIN) Datokarama Palu, 2024)
This study aims to identify and analyze the difficulties students face in solving problems related to the surface area and volume of prisms. The research employs a qualitative method, using data collection techniques such as observation, interviews, and document analysis involving 32 eighth-grade students at a public junior high school in Tasikmalaya. The data analysis technique used in this study is data triangulation. The findings reveal that 71.9% of students experience difficulties in understanding the basic concept of prisms, 34.3% struggle with applying formulas, and 15.6% have difficulty visualizing the shape of prisms. The discussion in this study emphasizes conceptual and procedural issues. The implications of this research significantly impact curriculum development and mathematics teaching methods in schools. Additionally, the findings can serve as a benchmark for educators in designing more effective learning strategies that focus on concept comprehension, visualization, and accurate formula application, as well as the development of more interactive teaching materials